PARAMETRIC INVESTIGATION OF SINGLE POINT INCREMENTAL FORMING OF COMMERCIAL ALUMINUM ALLOY - Anjali Shrikant Mulay; Ravi R. Navthar (International Journal of Innovations in Engineering Research and Technology, 2021)
Single point incremental forming (SPIF) is a new innovative and feasible solution for the rapid prototyping and the manufacturing of small batch sheet parts. In the present study experiments were conducted to analyze the effect of process parameters on the formability of commercial aluminum alloy AA1100. Major process parameters like Wall angle, Step increment, Feed rate, and Spindle speed, are set at three levels and experiments were designed by using the Taguchi method to get the two response parameters, wall thickness and surface finish. Analysis of variance shows that surface roughness depends on step increment by 64.19 % and wall angle by 17.23 %. For thickness reduction only wall angle (99.79 %) is responsible. For achieving better surface finish we need to control wall angle, step increment and feed rate while for thickness reduction we have to control only wall angle.